DISTRIBUTION OF PARTICULATE SULFUR IN THE WINTER ARCTIC STRATOSPHERE : BALLOON-BORNE MEASUREMENTS OF PARTICLE NUMBER CONCENTRATION - ワタナベ, マサハル; イワサカ, ヤスノブ; ハヤシ, マサヒコ; ナガタニ, マサヒロ; ナカダ, ヒロシ; アダチ, ヒロシ; フジワラ, モトオ; /; WATANABE, Masaharu; IWASAKA, Yasunobu; HAYASHI, Masahiko; NAGATANI, Masahiro; et al. (National Institute of Polar Research, 1997)
P(論文) Balloon-borne measurements of the size-number concentration of atmospheric particles were made in December 1994 and January 1995 at Ny-Alesund, Norway (79°N, 12°E). The measurements showed that the number concentration of stratospheric particles was 2 particles/(cm)^3 (particle diameter≧0.3μm) and 5×(10)^<-2> particles/(cm)^3 (particle diameter≧1.2μm) at the potential temperature height of 370K (near the height of the background aerosol layer peak) on December 18,1994,and 2 particles/(cm)^3 (particle diameter≧0.3μm) and 2×(10)^<-3> particles/(cm)^3 (particle diameter≧1.2μm) at the potential temperature height of 370K on January 17,1995. The number-size distribution function of the background sulfate particles showed noticeable decrease of particle concentration in the size range of 0.5-0.8μm in diameter in the heights of 350K-370K potential temperature from December 1994 to January 1995,suggesting that sulfate particles growing through up-take of water vapor descended in the winter polar stratosphere.The winter polar stratosphere functions as one possible sink in the global budget of atmospheric sulfur. departmental bulletin paper